Molecular Characterization of Diaporthe Species Associated With Hazelnut Defects - Arciuolo, Roberta; Santos, Carla; Soares, Célia; Castello, Giuseppe; Spigolon, Nicola; Chiusa, Giorgio; Lima, Nelson; Battilani, Paola (Frontiers in Plant Science, 2020)
Fungi of the genus Diaporthe have been reported as the main causative agent of hazelnut defects in the Caucasus area. This study aimed to define which fungal species are present in defective hazelnuts grown in Turkey and confirm the role of Diaporthe spp. Seven hazelnut orchards were selected, with each one located in a different Turkish province (Düzce, Girensun, Ordu, Samsun, Sakarya, Trabzon, and Zonguldak), and hazelnuts were collected at early and full ripening. Fungal isolation and identification were performed at the genus level based on morphological characteristics. Several genera were isolated, with Diaporthe spp. being among the prevalent. This was the only genus with increasing incidence from early to full ripening, and incidence at full ripening was positively correlated both with internal (ρ=0.86) and visible defects (ρ=0.81), which confirmed its role as the key causative agent of hazelnut defects. A total of 86 Diaporthe monosporic strains isolated from Turkish hazelnut samples, together with 33 strains collected in the Caucasus regions and 6 from Italy, were analyzed with a multi-locus phylogeny based on three genomic loci (ITS, EF1-α, and tub). The results showed that Diaporthe strains can be grouped into 7 distinct clades, with a majority of Turkish strains (95%) being placed into a single clade related with D. eres. These samples were organized into several sub-clades, which indicates the existence of genetically diverse sub-populations.